Correction: In situ growth of fluorescent silicon nanocrystals in a monolithic microcapsule as a photostable, versatile platform. Issue 37 (15th September 2016) - Zhu, Guixian; Huang, Yu; Bhave, Gauri; Wang, Yuzhen; Hu, Zhongbo; Liu, Xuewu
Abstract : Correction for ' In situ growth of fluorescent silicon nanocrystals in a monolithic microcapsule as a photostable, versatile platform' by Guixian Zhu, et al., Nanoscale, 2016, 8, 15645–15657.